Hubungan Riwayat Keluarga Dan Aktivitas Fisik Dengan Hipertensi Pada Ibu Hamil Di Puskesmas Asera - Harmawati Rustan (Window of Public Health Journal, 2025)
Hypertension in pregnant women is a serious health problem that contributes to high rates of maternal and fetal morbidity and mortality. This study, conducted at the Asera Community Health Center, North Konawe Regency, aimed to determine the relationship between family history and physical activity and hypertension incidence in pregnant women. The observational analytic study with a case-control design, involved 38 pregnant women as respondents selected through a total sampling technique. Data was collected using questionnaires and medical records, and then analyzed using the Chi-Square test. The results showed a significant relationship between a family history of hypertension (p = 0.000) and physical activity (p = 0.021) with the incidence of hypertension in pregnant women. The conclusion of this study is that a family history of hypertension and low physical activity increase the risk of hypertension in pregnant women. These findings have important implications for health promotion and prevention efforts, providing a basis for strategies to prevent complications of hypertension in pregnant women.